Molecular studies of the fragile X syndrome. - Knight, S; Hirst, M; Roche, A; Christodoulou, Z; Huson, S; Winter, R; Fitchett, M; McKinley, M; Lindenbaum, R; Nakahori, Y (1992)
We have studied families segregating for the fragile X syndrome for the presence of amplification of the CGG repeat sequence adjacent to the HpaII Tiny Fragment (HTF) island in the FMR-1 gene. We demonstrate that 138/143 fragile X positive, mentally retarded males show a characteristic smear of fragments corresponding to somatic variation in the amplification of the CGG sequence. In 7/8 normal transmitting males (NTM's), we show that there is a small amplification of sequence but no evidence for somatic variation. Defined mutated fragments in the size range found in NTM's are seen in daughters of NTM's. The daughters of these female carriers show either a defined fragment in the NTM size range, a defined larger fragment or a heterogeneous pattern of fragments. In the latter 2 cases the clinical phenotype of the females cannot easily be predicted, presumably because of variable X inactivation. In some families, the observed DNA genotype does not correlate with the phenotype; in others we demonstrate the occurrence of individuals with a mosaic DNA genotype. The implications of these data for diagnosis of the disease are discussed.